Servant Leadership Digital Hubungan Rekan Kerja Kolaboratif dan Motivasi terhadap Employee Engagement Gen Z CV. Anugrah Garment Wonogiri - Chicha Adita Maharani; Agus Suyatno; Indra Hastuti (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to analyze the mediating role of motivation in the relationship between digital servant leadership and collaborative coworker relationships on employee engagement among Generation Z employees at CV. Anugrah Garment Wonogiri. The focus of this study was directed at Gen Z employees working in the sewing department, with a sample of 79 respondents selected using a purposive sampling technique. This study used a quantitative approach with primary data obtained through the distribution of closed questionnaires. The variables used in this study include digital servant leadership as the first independent variable, collaborative coworker relationships as the second independent variable, motivation as the mediating variable, and employee engagement as the dependent variable. The data analysis technique was carried out using Structural Equation Modeling - Partial Least Square (SEM-PLS) through SmartPLS software version 4.0, which allows for the analysis of causal relationships between variables as well as simultaneous mediation tests. The results showed that digital servant leadership has a positive and significant correlation with employee engagement. Similarly, collaborative coworker relationships were shown to have a positive and significant correlation with employee engagement. In addition, motivation also has a positive and significant impact on employee engagement. Furthermore, digital servant leadership and collaborative coworker relationships each have a positive and significant impact on motivation. Furthermore, motivation has been shown to significantly mediate the influence of digital servant leadership on employee engagement, as well as collaborative coworker relationships and employee engagement. Therefore, it can be concluded that motivation plays a significant role as a mediator in strengthening the influence of leadership style and workplace social relationships on employee engagement, particularly among the younger generation working in the garment industry.